- #1

Subliminal1

- 16

- 0

*why*they were right and we were wrong- if someone could that would be great.

The equation with our working:

\(\displaystyle y=5\left(x+3\right)\)

\(\displaystyle \frac{y}{5}=x+3\)

\(\displaystyle \frac{y}{5}-3=x\)

We're told to do "the opposite" for this, so:

We isolated the variable (\(\displaystyle x\)) by dividing each side by factors that don't contain the variable (\(\displaystyle 5\)).

Then it's simple by subtracting \(\displaystyle 3\) from \(\displaystyle x\).

Replacing \(\displaystyle x\) with 2 as an example to test our result:

\(\displaystyle y=5\left(2+3\right)\) (or) \(\displaystyle y=5\)x\(\displaystyle 5\) (or) \(\displaystyle y=25\)

\(\displaystyle \frac{25}{5}=5\), \(\displaystyle −3=2\), \(\displaystyle x=2\)

Even Mathway gives the same working, so I'm a little lost. I can't remember exactly what our lecturer said the answer was, I believe it was \(\displaystyle y=1.2\), but as I said they wouldn't tell us

*how*they calculated that.

I have posted this question on a couple of other sites as it's still sat in the moderation queue on the first one we tried.

Thanks